2023
DOI: 10.1021/acsnano.3c02041
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Proteins Determining the Blood Circulation Time of Nanoparticles

Abstract: The therapeutic efficacy and adverse impacts of nanoparticles (NPs) are strongly dependent on their systemic circulation time. The corona proteins adsorbed on the NPs determine their plasma half-lives, and hence, it is crucial to identify the proteins shortening or extending their circulation time. In this work, the in vivo circulation time and corona composition of superparamagnetic iron oxide nanoparticles (SPIONs) with different surface charges/chemistries were analyzed over time. SPIONs with neutral and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…In contrast, if more dysopsonins are adsorbed, then nanoparticles can have more time and a higher opportunity to reach the target tissues. Moreover, Maurizi et al identified the hard corona proteins that determine the retention time of superparamagnetic iron oxide nanoparticles in the blood circulation system. It was found that the protein corona composition, such as hemoglobin, can regulate the circulation time and clearance of these ultrasmall nanoparticles, and the increased content of hemoglobin on the surfaces of positively charged nanoparticles dictated most of the circulation time.…”
Section: Features Of the In Vivo Protein Corona Formation Of Nanopart...mentioning
confidence: 99%
“…In contrast, if more dysopsonins are adsorbed, then nanoparticles can have more time and a higher opportunity to reach the target tissues. Moreover, Maurizi et al identified the hard corona proteins that determine the retention time of superparamagnetic iron oxide nanoparticles in the blood circulation system. It was found that the protein corona composition, such as hemoglobin, can regulate the circulation time and clearance of these ultrasmall nanoparticles, and the increased content of hemoglobin on the surfaces of positively charged nanoparticles dictated most of the circulation time.…”
Section: Features Of the In Vivo Protein Corona Formation Of Nanopart...mentioning
confidence: 99%
“…5 However, it works as an iron supplement instead of a T 2 MRI contrast agent nowadays owing to its relatively low T 2 contrast and undesirable behavior in vivo. 2,6,7 Therefore, developing effective strategies to enhance the contrast efficiency of IONP-based materials has become an urgent demand as they can be translated into clinical applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We showed that both protein content and composition change over time in the animal body ( in vivo experiments). 16 The protein exchange on the NPs affects their retention time in the blood circulation system. Any changes in the content of proteins extending (dysopsonins) and/or shortening (opsonins) the NP circulation time can affect the plasma half-life of NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Any changes in the content of proteins extending (dysopsonins) and/or shortening (opsonins) the NP circulation time can affect the plasma half-life of NPs. 16 Opsonins are a group of proteins that enhance the phagocytosis of foreign particles by immune cells, such as macrophages and neutrophils. Opsonization of nanoparticles can lead to their rapid clearance from circulation and accumulation in the liver and spleen, which can limit their therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation